Analisis Kepatuhan Pengusaha Kena Pajak Dalam Menyampaikan SPT Masa PPN Tahun 2010 - Marpaung, Annaria Magdalena; Budianto, Enjang Tachyan (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2012)
Tax is one of the largest sources of funding for a state. Tax emerges as an effort to cover all state expenditures and to finance a countryâs development. Value added tax (VAT) is tax imposed on the delivery or import of taxable goods and services conducted by the taxable company and it can be imposed many times whenever the value added abides and it can be credited. The purpose of this study is to determine how to calculate the value added tax at PT Pilar Multi Sentosa as well as to determine the adherence stage of PT Pilar Multi Sentosa (the taxable company) in conveying SPT ofvalue added tax period after the change of VAT Law 2010. The result of this study shows that PT Pilar Multi Sentosa as one of taxable companies adheres in conveying SPT of value added tax period 2010 because it has paid and reported the tax on time. PT Pilar Multi Sentosa was established in 1999 and located in Baranang Siang Indah, Jalan telaga Warga I, Blok B 1 No. 17, RT/RW 04/05, Katulampa, East Bogor subdistrict. The company engages in the field of buildings developinng or popularly called cantractor. Its Taxpayer Identification Number (TIN) â Nomor Pokok Wajib Pajak (NPWP) â is 02.740.584.4.404.000.